High availability for the LAMP Stack - Cannon, Jason; Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2018)
"This step-by-step guide teaches you everything you need to know in order to eliminate single points of failure for your Linux, Apache, MySQL, and PHP based web applications. This is a full blown course that demonstrates everything step-by-step. This is not just a design, though. It's an entire course complete with lessons and demonstrations on actual Linux servers. I'll be performing the demonstrations on Ubuntu servers, but the concepts are the same no matter if you're using RedHat Enterprise Linux, CentOS, or another distribution. The only real difference is the couple of commands you'll use to perform some of the software installations. The design and configurations remain the same. Even though this course is targeted directly at the LAMP stack (Linux, Apache, MySQL, PHP), the concepts and techniques presented can be reused in a variety of other situations. If you ever need a floating IP, the ability to add more storage to servers without downtime, to balance loads across multiple servers, or deploy a highly available database cluster, you can put what you learn in this course to good use."--Resource description page.
Presenter, Jason Cannon.
Title from resource description page (Safari, viewed March 6, 2018).
Keywords: Linux; Apache (Computer file : Apache Group); MySQL (Electronic resource); Web site development; Open source software; PHP (Computer program language); Electronic books